Relational Teaching Behaviours in the Large University Class: An Observational Study - Simon G. Beaudry; Jenepher Lennox Terrion; Meredith Rocchi; Michelle Bartleman (Canadian Journal for the Scholarship of Teaching and Learning)
Larger class sizes in higher education can generate many challenges for educators, notably increased negative student evaluations of teaching. This study suggests that one strategy for countering some of the shortcomings of the large classroom is to take a relational teaching approach. We coded the relational communication behaviours of professors teaching in large in-person classrooms and found that encouraging participation as well as having a relaxed body position were most prevalent among instructors with typically high course evaluation ratings. In addition, correlations between relational teaching behaviours and students’ course evaluation reports found that instructors with the highest scores were more likely to make eye contact and to smile. We argue that relational teaching behaviours may have an impact on students’ perceptions of teaching quality. These findings provide insights into more effective relational teaching in the large class, in particular demonstrating that the most prevalent relational teaching behaviours are not necessarily the most important or effective.